ANALISIS LAPORAN KEUANGAN SEBAGAI ALAT PENGUKURAN KINERJA KEUANGAN PADA PERUSAHAAN PERSEROAN (PERSERO) P.T.TELEKOMUNIKASI INDONESIA TBK DAN ANAK PERUSAHAAN - Soetarmiyati, Nani (Jurnal Manajemen dan Keuangan, 2012)
Accounting is a discipline that provides the information necessary to perform efficiently and evaluate the activities organization.Was when viewed from the Accounting activity is the process of recording, classifying, summarying, report and analyze financial data of the organization. This can be reflected in the financial statements. Financial Report is an overview of the companys financial condition at any given moment. The instrument used for the analysis of financial condition as follows: Balance Sheet and Income Statement. The aim is to assess the financial performance of PT Telkom. From the analysis of the ratio of Consolidated Financial Corporation (Corporation) PT. Telekomunikasi Indonesia Tbk and Subsidiaries illustrate that any analysis of 2006-2010 the ratio is still below the industry standard ratio. This resulted in financial performance has not been good.Keywoards : Liquidity, Laverage, and Profitability Activity